103 Puberty induction protocol, but not supplement amount, overcomes the negative impacts of reduced frequency of supplementation on reproduction of beef heifers. (29th July 2019) - Ranches, Juliana; Vedovatto, Marcelo; Palmer, Elizabeth; Miranda, Miguel; Arthington, John; Vendramini, João; Moriel, Philipe
Abstract: This study evaluated the performance of Bos indicus-influenced beef heifers submitted to a puberty induction protocol and offered two supplementation amounts and delivery frequencies. Sixty-four Brangus crossbred heifers were stratified by BW and age (244 ± 4 kg; 311 ± 18 d) and assigned into 1 of 16 bahiagrass pastures on d 0. Treatments were randomly assigned to pastures in a 2 × 2 factorial design (4 pastures/treatment) and consisted of soyhulls-based supplementation at 1.25% or 1.75% of BW (DM basis) offered daily or 3 times weekly for 168 d. The puberty induction protocol consisted of CIDR insert on d 56 and removal on d 70, 5-mL PGF2a injection on d 86, 2-mL GnRH injection and timed-AI on d 89. Heifers were exposed to Angus bulls from d 89 to 167 (1 bull/pasture). Pregnancy diagnosis was assessed on d 212. Frequency × rate effects were not detected (P ≥ 0.19) for any variable. Reducing the supplementation frequency from daily to 3X weekly tended (P = 0.07) to decrease overall ADG and puberty attainment on d 56 (53 vs. 41 ± 6%), but not puberty attainment on d 89 (P = 0.45; 84 vs. 78 ± 6%) and pregnancy percentage on d 212 (P = 0.97; 69 vs. 69 ± 7%). Increasing the supplement amount from 1.25% to 1.75% of BW increased (P = 0.04) overall ADG, tended (P = 0.09) to hasten puberty attainment on d 56 (40 vs. 54 ± 6%) and d 89 (74 vs. 88 ± 6%), and enhanced (P = 0.03) pregnancy percentage on d 212 (53 vs. 80 ± 7%). Therefore, the inclusion of a puberty induction protocol, but not increasing the supplement amount, enabled a reduced frequency of supplementation (3 vs. 7 times weekly) without detrimental impacts on percentage of pregnant yearling beef heifers.